2015
DOI: 10.3389/fphys.2015.00073
|View full text |Cite
|
Sign up to set email alerts
|

Leucine minimizes denervation-induced skeletal muscle atrophy of rats through akt/mtor signaling pathways

Abstract: The aim of the present study was to evaluate the effect of leucine treatment (0.30 mM) on muscle weight and signaling of myoproteins related to synthesis and degradation pathways of soleus muscle following seven days of complete sciatic nerve lesion. Wistar rats (n = 24) of 3–4 months of age (192 ± 23 g) were used. The animals were randomly distributed into four experimental groups (n = 6/group): control, treated with leucine (L), denervated (D) and denervated treated with leucine (DL). Dependent measures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…This result agrees with some human studies showing that infusion of BCAA suppressed muscle protein breakdown without increasing protein synthesis, although species differences may be present [ 39 40 ]. In contrast with our results, leucine increased the phosphorylation of Akt and mTOR against denervation induced muscle atrophy in middle aged rats [ 29 ]. These results suggest that although BCAA administration did not increase the levels of Akt1 and mTOR mRNA, it has the potential to affect the activation of Akt1 and mTOR at the protein level.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result agrees with some human studies showing that infusion of BCAA suppressed muscle protein breakdown without increasing protein synthesis, although species differences may be present [ 39 40 ]. In contrast with our results, leucine increased the phosphorylation of Akt and mTOR against denervation induced muscle atrophy in middle aged rats [ 29 ]. These results suggest that although BCAA administration did not increase the levels of Akt1 and mTOR mRNA, it has the potential to affect the activation of Akt1 and mTOR at the protein level.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, it is well known that BCAA plays a pivotal role in protein synthesis through the direct activation of mTOR without the activation of upstream signaling molecules like IGF-1 and Akt1 [ 28 ]. However, recent study shows that leucine activates Akt as well as mTOR [ 29 ]. Akt, also known as protein kinase B (PKB), has emerged as a critical mediator of mTOR activity.…”
Section: Discussionmentioning
confidence: 99%
“…While p-Akt content was elevated, the difference between treatments was not significant. Despite this observation, leucine has previously been repeatedly shown to enhance insulin signaling through increased Akt activity [24][25][26][27][28][29][30]. This is of profound significance, as GLUT4 membrane content is tightly regulated by insulin signaling following carbohydrate-rich meals.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 83%
“…Several recent clinical studies have indicated that dietary supplementation with branched-chain amino acids (BCAA), particularly with leucine, is an effective anti-atrophic therapy (Bauer et al, 2015 ; Tsien et al, 2015 ; English et al, 2016 ). In animal models, BCAA can prevent denervation (Ribeiro et al, 2015 ), hindlimb suspension (Maki et al, 2012 ; Jang et al, 2015 ) or dexamethasone-induced (Yamamoto et al, 2010 ) muscle atrophy. General control nonderepressible 2 kinase (GCN2) is a well-known amino-acid sensor.…”
mentioning
confidence: 99%